Diminished ovarian reserve versus ovarian aging: overlaps and differences. Issue 3 (June 2019) - Ata, Baris; Seyhan, Ayse; Seli, Emre
Abstract : Purpose of review: Diminished ovarian reserve, in general, implies a quantitative decline in the oocyte pool. However, whether this quantitative decline is necessarily accompanied by a qualitative decline, remains to be determined. Recent findings: Studies of natural conception suggest that fecundity of women with a quantitative decline in ovarian reserve is similar to age-matched women with normal ovarian reserve. Data on rates of pregnancy loss and fetal chromosomal abnormality do not consistently suggest a decline in oocyte quality in women who has a lower ovarian reserve. In assisted reproductive technology (ART) cycles, oocytes from women with diminished ovarian reserve have similar potential for euploid blastocyst development. Likewise, available evidence does not strongly suggest an increased risk of pregnancy loss in women with diminished reserve undergoing ART treatment as compared with similarly aged woman with normal ovarian reserve. Summary: Quantitative decline in ovarian reserve may not be necessarily accompanied by a qualitative decline. Although a decreased number of follicles and poor response to ovarian stimulation are hallmarks of ovarian aging, younger women with diminished ovarian reserve may not be experiencing the distinct effects of aging on oocyte quality.